Mechanism of Hepatoprotective Effect of Boesenbergia rotunda in Thioacetamide-Induced Liver Damage in Rats. (7th August 2013) - Salama, Suzy M.; Abdulla, Mahmood A.; AlRashdi, Ahmed S.; Hadi, A. Hamid A.
Abstract : Background . Researchers focused on developing traditional therapies as pharmacological medicines to treat liver cirrhosis. Objectives . Evaluating the hepatoprotective activity of Boesenbergia rotunda (BR) rhizome ethanolic extract on thioacetamide-induced liver cirrhosis in rats. Methods . Male Sprague-Dawley rats were intraperitoneally injected with 200 mg/kg TAA 3 times/week and daily oral administration of 250 mg/kg, 500 mg/kg of BR extract, and 50 mg/kg of the reference drug Silymarin for 8 weeks. At the end of the experiment, Masson's trichrome staining was used to measure the degree of liver fibrosis. Hepatic antioxidant enzymes (CAT and GPx), nitrotyrosine, cytochrome (P450 2E1), matrix metalloproteinase (MMP-2 and MMP-9), tissue inhibitor of metalloproteinase (TIMP-1), and urinary 8-hydroxyguanosine were measured. Serum levels of transforming growth factor TGF- β 1, nuclear transcription factor NF- κ B, proinflammatory cytokine IL-6, and caspase-3 were evaluated. Serum protein expression and immunohistochemistry of proapoptotic Bax and antiapoptotic Bcl-2 proteins were measured and confirmed by immunohistochemistry of Bax, Bcl-2, and proliferating cell nuclear antigen (PCNA). Results . BR treatment improved liver histopathology, immunohistochemistry, and biochemistry, triggered apoptosis, and inhibited cytokines, extracellular matrix proteins, and hepatocytes proliferation. Conclusion . Liver cirrhosis progression can be inhibited by the antioxidant and anti-inflammatory activities of BR ethanolic extract while preserving the normal liver status.